2010
DOI: 10.1557/jmr.2010.0275
|View full text |Cite
|
Sign up to set email alerts
|

Numerical approaches and experimental verification of the conical indentation techniques for residual stress evaluation

Abstract: Conical indentation methods to determine residual stress are proposed by examining the finite element solutions based on the incremental plasticity theory. We first note that hardness depends on the magnitude and sign of residual stress and material properties and can change by up to 20% over a specific range of elastic tensile and compressive residual stress, although some prior indentation studies reported that hardness is hardly affected by residual stress. By analyzing the characteristics of conical indent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Thereupon, we set f = 0.3, since Coulomb friction coefficient between general metals is about 0.1-0.4. Lee (2006) contrived a way of minimizing the frictional effect on estimated properties by suitably selecting the regression range of strain, the summary of which is given in Section 5.2. If we use low h max /D, because of relatively small indentation load and contact area for a given indenter radius, we can reduce specimen size and minimize deformation of indenter.…”
Section: Comparison Of the Characteristics Between Shallow And Deep Imentioning
confidence: 99%
See 1 more Smart Citation
“…Thereupon, we set f = 0.3, since Coulomb friction coefficient between general metals is about 0.1-0.4. Lee (2006) contrived a way of minimizing the frictional effect on estimated properties by suitably selecting the regression range of strain, the summary of which is given in Section 5.2. If we use low h max /D, because of relatively small indentation load and contact area for a given indenter radius, we can reduce specimen size and minimize deformation of indenter.…”
Section: Comparison Of the Characteristics Between Shallow And Deep Imentioning
confidence: 99%
“…With Young's modulus still fixed, varying yield strain through its entire range in Table 2 then makes the coefficients as double polynomial functions of strainhardening exponent and yield strain. Note that for each value of varying yield strain, strain-hardening exponent varies again through its entire range in Table 2 1.5, 2, 2.5, 3, 4, 5, 7, 10, 13, 20, 50 formulas for three normalized indentation variables (Lee, 2006). We also plotted the regression lines generated from Eqs.…”
Section: Numerical Formulas For Deep Spherical Indentation Techniquesmentioning
confidence: 99%
“…However, the sensitivity of C to RS is rather low here (especially in combination with a high n), making the approach less appropriate for these materials. Lee et al [22] found for conical indentation that the maximum load (or C) for indentation on a specimen with σ R1 and σ R2 is equal to the mean average of the maximum loads (or C) from two indentations (same depth) on specimens with equibiaxial RS σ RI = σ R1 and σ RII = σ R2 . Assuming that this holds also for Knoop indentation, we can write in terms of Kick's law coefficients in a similar fashion …”
Section: Residual Stress Ratiomentioning
confidence: 99%
“…Further, the finding that C values for the non-equibiaxial RS case can be converted to equivalent C values for two equibiaxial RS cases, made for conical indentation (J.H. Lee et al, 2010, J Mater Res 25: 2212-2223, is shown to apply to Knoop indentation, too. The magnitude of RS can thus be determined from the equibiaxial RS case.…”
mentioning
confidence: 94%
See 1 more Smart Citation